THE OVERVIEW OF KNOWLEDGE LEVEL OF FEVER SELF - MEDICATION AT SUKAJADI PHARMACY INDRAMAYU FOR THE JUNE - JULY 2023 PERIOD - Neni Rahmani Neni; Dela Puspita (Jurnal Farmasi IKIFA, 2024)
Background : Self-medication is an effort made by the community to treat symptoms of illness or diseaseby using drugs without a doctor's prescription, while fever is a condition where the body temperature is above normal, namely body temperature above 37 ℃. Purpose : This study aims to determine the level of knowledge of respondents about fever and self-medication at Sukajadi Pharmacy. Methode : This study uses non- experimental research with the type used is descriptive qualitative with a cross sectional approach design. Sampling was taken when the patient bought medicine at the Sukajadi Pharmacy. The research instrument used a questionnaire, using a sample of 100 people. Respondents usedin this study ranged in age from 18 years -> 41 years which was the inclusion criteria. Result : The results showed that the most respondents who self-medicated were women (75%) aged > 21 years and over (56%) with high school education level (57%) and working as housewives (30%). Thedescription of self-medication actions shows that the drug that most respondents choose is the sanmol brand, the paracetamol content is 40% and 85% buys it at the pharmacy, 60% chooses their own medicineand the reason respondents do self-medication is supporting factors (easy to get, cheap, close treatment distance). ). Conclusion : This shows that the description of the level of knowledge of the respondents has gone well as much as 92%, enough knowledge as much as 8% and less as much as 0%